Ethnic Identity and Parenting Stress in South Asian Families: Implications for Culturally Sensitive Counselling - Shariff, Aneesa (Canadian Journal of Counselling and Psychotherapy, 2009)
The South Asian culture is one in which family obligation and loyalty, as well as self-sacrifice and obedience toward one’s elders, are paramount. These values can be different from those of the more individualistically oriented Euro-Canadian dominant culture, and can prompt challenges of cultural adjustment among Canadian-born South Asian youth and their immigrant parents. This article describes adolescent ethnic identity formation and parenting stress as two common issues for South Asian families in counselling. The article also presents culturally informed recommendations for addressing these issues, ending with a case illustration to highlight the use of these interventions in practice.